Border Security Problems in the Waters of the Natuna Islands: Between National Boundaries and Illegal Fishing - Fauzan Fauzan; Kamarulnizam Abdullah; Mohammad Zaki Ahmad (AEGIS : Journal of International Relations, 2019)
Natuna or better known as the Natuna Islands is one of the border areas in Indonesia that has complex problems. As a cluster of islands bordering Indonesia with Malaysia and Vietnam, the Natuna Islands are also located in the South China Sea region, which is a regional dispute hot spot in East Asia. This paper will discuss the concept of border security and border security issues in the waters of the Natuna Islands. In this paper, the authors argue that the problem of the Indonesian EEZ maritime boundary in the Natuna Islands territorial waters with Malaysia and Vietnam needs to be immediately resolved, because in addition to sovereignty, the precision of the EEZ boundary with neighboring countries will be related to the management of natural resources contained in the particular territorial waters. This condition is increasingly complicated when China with its nine-dashed line has raised problems of overlapping claims in the Natuna waters. In addition, the obscurity of maritime boundaries is used by certain parties to carry out illegal fishing in the maritime areas currently being disputed by the neighboring countries.